Reykjavik District Heating - Lienau, Paul J. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1977)
The number of inhabitants of Reykjavik and its suburbs benefiting from geothermal heating are 109,829 living in 15,614 homes and apartments or 97.1 percent of the population of the city. Converted into units of energy, the sales of hot water in 1976 corresponded to 1840 GWh, which is equivalent to burning some 1.1 million barrels of fuel oil. Discussion is centered on production from wells in the Reykin and Reykajahlid field, the distribution system, insulation, and regulations and price. It is pointed out that the savings to district heating customers is 25 to 30 percent when compared to fuel oil costs